PENGHITUNG JUMLAH ORANG MASUK DAN KE LUAR BERBASIS IoT DILENGKAPI PENGUKUR SUHU TUBUH - I Putu Indra Pramana Yoga; I Gusti Agung Komang Diafari Djuni H; Nyoman Pramaita (Program Studi Teknik Elektro UNUD, 2022)
As a precaution against the spread of the Covid-19 virus in public facilities, thegovernment requires to measure temperature and limit the number of people in order to preventnew clusters, especially in crowded centers. To reduce this problem, a prototype of the numberof people entering and leaving through the IoT-based door will be made using an ultrasonicsensor HCSR-04 equipped with a body temperature meter. This system works from reading thetemperature sensor value MLX90614, when the temperature is above 37oC then the doorremains closed and when the temperature is below 37oC the door will open, ultrasonic sensor 1is placed on the entrance side and ultrasonic sensor 2 is placed on the exit side, if the sensor 1receives one input, the system will automatically add a variable number of visitors, if sensor 2receives one input, the system will automatically reduce the variable number of visitors, andwhen the room is full of 10 people, the servo motor will close the door automatically, informationon body temperature and total person data will be displayed on the LCD and the Blynkapplication and sent to the MySql webserver database in real time. The prototype system thathas been made is capable of detecting body temperature and counting the number of peopleentering and leaving the door according to the design.